11TH GRADE STUDENTS’ PERCEPTION OF THE FACTORS AFFECTING THEIR ENGLISH LEARNING - Montero, Katherin Del Carmen Rodríguez; Ramos, Pastor Pablo Pérez (Seven Editora, 2025)
The English language holds great relevance worldwide. In recent decades, proficiency in this language has provided access to various opportunities in academic, professional, and cultural fields. At the secondary level, English language learning is influenced by both internal and external factors. The objective of this research is to analyze the perceptions of 11th-grade students regarding the factors that influence their learning of the English language. The study is framed within the quantitative paradigm, applying a non- experimental, cross-sectional descriptive approach. The results show that the factors that most affect English language learning among 11th-grade students are: the instrumental value of the language (future, travel, resources), motivation and personal confidence (self- efficacy vs. anxiety), pedagogical practices (activities, materials, teacher’s role), and extracurricular habits (low exposure to authentic English). In conclusion, 11th-grade students recognize the value of English for their future lives and are aware of the factors that influence their learning of the language.DOI: https://doi.org/10.56238/sevened2025.038-025